1993
DOI: 10.1002/jor.1100110613
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of fretting corrosion of Ti‐6Al‐4V by various surface treatments

Abstract: Titanium and titanium-6% aluminum-4% vanadium (Ti-6Al-4V) are known to be biocompatible and corrosion resistant. However, there have been numerous reports of elevated tissue levels of titanium due to passive dissolution, wear, or fretting corrosion of implants. Studies were undertaken to determine whether the fretting corrosion of Ti-6Al-4V could be reduced by surface treatment of one or both surfaces in a fretting situation. Three different surface treatments were studied: ion implantation, physical vapor dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Several studies (Maurer et al. ; Narayanan et al. ) have reported the effectiveness of EIS models in estimating the protectiveness of the oxide film formed on the Ti surface as a function of saliva pH levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Maurer et al. ; Narayanan et al. ) have reported the effectiveness of EIS models in estimating the protectiveness of the oxide film formed on the Ti surface as a function of saliva pH levels.…”
Section: Resultsmentioning
confidence: 99%
“…Impedance experimental data were fitting with chisquare error <0.001 (Valero Vidal & Igual Muñ oz 2008). Several studies (Maurer et al 1993;Narayanan et al 2007) have reported the effectiveness of EIS models in estimating the protectiveness of the oxide film formed on the Ti surface as a function of saliva pH levels. The evolution of C dl and R p are presented in Fig.…”
Section: Eis Measurementsmentioning
confidence: 99%
“…Thus, a great deal of research has been performed on the orthodontic materials and has provided warning on the adverse effects of corrosion. (1) Shot-peening or nitriding: It has been recently shown that nitriding can reduce the magnitude of fretting corrosion of Ti-6AI-4V devices [80]. (2) Ion implantation: Implantation of ions helps to harden the surface and improve the resistance to wearaccelerated corrosion phenomenon.…”
Section: Corrosion In Dentistrymentioning
confidence: 99%
“…Regardless, the properties of the resulting films are greatly influenced by the processing parameters of time, temperature, and pressure. Unfortunately, only a few studies [13][14][15] have investigated the effect of surface modification on the fretting corrosion of modular implants. In these studies, nitrogen ion implantation and various forms of nitriding were used to deposit titanium nitride (TiN) diffusion layers onto Ti6Al4V substrates.…”
Section: Introductionmentioning
confidence: 99%